KONTRIBUSI KEPEMIMPINAN VISIONER KEPALA SEKOLAH DAN PELAKSANAAN SUPERVISI TERHADAP EFEKTIVITAS SEKOLAH DASAR (SD) DI KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR - Sariakin Sariakin; Nora Fitria (Jurnal Ilmiah Global Education, 2023)
As an institution, schools are intended to produce academic graduates who have talent and character. High management standards, as well as openness, responsibility, and accountability, are characteristics of effective schools. Efficient schools serve as the best learning environments while providing high-quality teaching. In this study, the principal's initiative was carried out to support teachers and staff in improving the learning process and developing a better teaching and learning environment to achieve academic goals. The implementation of the principal's supervision, the principal's inspirational leadership, and school success are the three variables included in this study. The research was conducted through quantitative research techniques. Each variable can be explained individually thanks to this investigation. The relationship between different variables is evaluated using correlation. 36 elementary school teachers from Darul Imarah sub-district, Aceh Besar district participated in this study. The research findings show that visionary leadership has an average impact on school effectiveness of 4.44. The partial correlation coefficients for school effectiveness are 0.545 and 0.397, respectively. When compared with the principal's visionary variable, the supervisory performance of the principal has a stronger partial correlation coefficient. Substantial correlations were found between Principal Visionary Leadership (X2) 0.399, Principal Supervision Implementation (X1) 0.033, and School Effectiveness (Y) 0.00.